Adaptation and evaluation of the Finnish version of the Recovery-Stress Questionnaire for Athletes - Pennanen, Felix (2018)
An optimal balance between physical stress and recovery is essential to athletic performance. Athletes have to balance physical stress and recovery time to avoid overtraining, fatigue and injury. The optimal balance between athletes’ stress and recovery can be monitored and maintained through different methods, from physiological measures to psychometric instruments (Kellman, 2010). A commonly used psychometric tool is the Recovery–Stress Questionnaire for Athletes (RESTQ-Sport) developed by Kellman and Kallus (2001). The RESTQ-Sport has been applied in a number of studies (Kellman, 2010), and both validity and reliability has been proven high for the original English version (Kellman & Kallus, 2001). However, there is no version in Finnish language.